A IMPACT OF A PHARMACIST-LED EDUCATIONAL INTERVENTION ON QUALITY OF LIFE AMONG PATIENTS WITH ASTHMA - QUYNH THI HUONG BUI; KHOI XUAN PHAM; TIEN HOANG TRAN; LAN THI TUYET LE; HO NHU NGUYEN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Asthma is a chronic disease resulting in reduced quality of life (QoL) of most affected individuals. Training in asthma-related knowledge, inhaler skills, medicine usage, and the prevention of adverse drug events is demonstrated to improve asthma patients’ QoL. Therefore, the research was conducted to evaluate the effectiveness of education intervention undertaken by pharmacists on QoL of patients with asthma. Methods: We conducted a clinical randomized controlled trial among asthmatic outpatients aged 18 years or older in the Department of Screening Respiratory Function, University Medical Center, Ho Chi Minh City, Vietnam. Patients were randomized into an intervention group (IG) and a non-IG (NIG). The clinical pharmacists’ intervention program included training in asthma-related knowledge, inhaler technique, recognition, prevention of adverse drug events, and lifestyle adjustment. Participant screening was conducted using the telephone on a monthly basis. QoL was measured using the Vietnamese Version of the Mini Asthma QoL Questionnaire (MiniAQLQ). The main outcome was the difference in QoL scores between IG and NIG after 3 months follow-up. Results: After 3 months, the number of patients with asthma in the IG and in the NIG was 173 and 96, respectively. QoL mean scores in the IG patients were significantly higher than those in their NIG counterparts (1.79±1.01 vs. 1.06±0.93, respectively, p<0.001). Pharmacist-based interventions overall QoL scores (multivariate-adjusted regression coefficient =0.362; p<0.001). Conclusions: Clinical pharmacist-led counseling can improve asthmatic patients’ QoL.